Pelatihan Metode SPEOS (Stimulasi Pijat Endhorpin, Pijat Oksitosin dan Sugesti) Ibu Nifas Pada Tim Pendamping Keluarga di Wilayah Puskesmas Danau Marsabut Kecamatan Sipirok - Meidiawaty Siregar; Ganti Tua; Herawati Harahap (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Based on the 2018 Riskesdas results, the proportion of breastfeeding patterns for babies aged 0-5 months in Indonesia is 37.3% exclusive breastfeeding, 9.3% partial breastfeeding and 3.3% predominant breastfeeding. Predominant breastfeeding is breastfeeding the baby but giving a little water or a water-based drink, for example tea, as a prelacteal food/drink before the milk comes in. Meanwhile, partial breastfeeding is breastfeeding a baby and giving artificial food other than breast milk such as formula milk, porridge or other food before the baby is 6 months old, whether given continuously or as prelacteal food. North Sumatra Province Nutrition Program Data in 2018. The percentage of exclusive breastfeeding for babies 0-6 months in North Sumatra in 2018 was 65.57 percent, an increase compared to the percentage of exclusive breastfeeding in 2017, namely 54.4 percent (Sumatra Provincial Health Service, 2017). 2018). In the breastfeeding process, problems sometimes arise that can prevent giving breast milk to babies. Problems that mothers often experience when breastfeeding include inverted nipples, swollen breasts, sore and painful nipples, blocked milk ducts, breast inflammation and insufficient milk production (Purwoastuti, 2015). There are many non-pharmacological methods that can help postpartum mothers increase breast milk production, ranging from marmet massage, oxytocin massage, Woolwich massage to areola and rolling massage. Currently, based on the results of related research, there are non-pharmacological methods that are cheaper, easier, non-invasive and acceptable to respondents and without side effects. Nursing interventions that can be applied to help increase lactation in post partum mothers are the SPEOS method (Endorphin, Oxytocin and Suggestive Massage Stimulation).